2014
DOI: 10.1037/a0034260
|View full text |Cite
|
Sign up to set email alerts
|

Increasing colonoscopies? A psychological perspective on opting in versus opting out.

Abstract: Although modifying the default to an opt-out system has been shown to be effective in some health care procedures, the current results reveal this system is not always effective in producing the healthiest medical behaviors. Our research, then, suggests that opt-out paradigms are not an overall panacea for increasing participation in preventive health. (PsycINFO Database Record (c) 2014 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Our finding that appointment lead time, season of referral, and opt-out scheduling were significantly associated with missed appointment rates is consistent with prior studies documenting similar associations in outpatient endoscopy settings, 8,10,12,14,18 and our finding that marital status, residence, drive time, and comorbidities were associated with at least 1 of the outcomes examined is consistent with prior studies documenting similar associations in general practice settings. [28][29][30] However, some of our findings contrast with findings from prior studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that appointment lead time, season of referral, and opt-out scheduling were significantly associated with missed appointment rates is consistent with prior studies documenting similar associations in outpatient endoscopy settings, 8,10,12,14,18 and our finding that marital status, residence, drive time, and comorbidities were associated with at least 1 of the outcomes examined is consistent with prior studies documenting similar associations in general practice settings. [28][29][30] However, some of our findings contrast with findings from prior studies.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies examining factors associated with missed and cancelled appointments in outpatient endoscopy clinics have identified a number of predictors, including patient age [8][9][10][11][12] and gender, 13 appointment lead time (ie, number of days between the scheduling date and appointment date), 8,10,12 season of referral, 14 and organizational-level improvement strategies such as appointment reminders, 8,[15][16][17] opt-in scheduling (ie, requiring patients to call to initiate scheduling), 18 and peer coaching. 11 To our knowledge, no prior studies examining outpatient endoscopy clinic appointments have distinguished between cancelled and missed appointments.…”
Section: See Editorial On Page 268mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rates of organ transplantation are higher in countries with opt‐out preference indication for organ donation (presumed consent) than in countries with opt‐in preference indication (explicit consent) 27. In some studies, participant recruitment has been shown to be enhanced by an opt‐out structure,28 while in others, an opt‐out structure may have caused perceived loss of autonomy that led to reduced recruitment 29. On the other hand, preselection of orders (“default to prescribe” mode) within order sets has in some contexts dramatically increased prescription rates,30 but such practices have the potential to infringe on provider autonomy and may increase the potential for errors (eg, automatic prescription despite an allergy or drug interaction known to the provider).…”
Section: Discussionmentioning
confidence: 99%
“…27 In some studies, participant recruitment has been shown to be enhanced by an opt-out structure, 28 while in others, an optout structure may have caused perceived loss of autonomy that led to reduced recruitment. 29 On the other hand, preselection of orders ("default to prescribe" mode) within order sets has in some contexts dramatically increased prescription rates, 30 but such practices have the potential to infringe on provider autonomy and may increase the potential for errors (eg, automatic prescription despite an allergy or drug interaction known to the provider). In the intervention analyzed in our study, the change from opt-in to opt-out was introduced with a relatively "soft touch" (a requirement to address the statin section) that maintained provider autonomy and yet was still associated with increased prescribing behavior.…”
Section: Discussionmentioning
confidence: 99%